2019
DOI: 10.52372/kjps34206
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Role of Culture in Policy Transfer: A Dynamic Policy Transfer Model

Abstract: Anticorruption policy transfer has been discussed for decades, but the influence of culture in target countries has not received comparable attention sufficient to explain the lack of progress in reducing corruption in those countries. The conceptualization of culture so far has provided only a limited tool for developing a dynamic theory of policy transfer. We propose a bottomup model of dynamic policy transfer that takes into account the cultural context in target countries. We first define culture as a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The first is to prevent sexual violence by carrying out a series of institutional arrangements and also to provide certainty to obtain social justice for victims as well as perpetrators. Some elements of the policy are translated while others are not, demonstrating that policy is never objective (Ady & Choi, 2019;Paris et al, 2011). This study also revealed that the policy transfer phase produces novel outcomes from policy innovation and knowledge transfer.…”
Section: Discussionmentioning
confidence: 74%
“…The first is to prevent sexual violence by carrying out a series of institutional arrangements and also to provide certainty to obtain social justice for victims as well as perpetrators. Some elements of the policy are translated while others are not, demonstrating that policy is never objective (Ady & Choi, 2019;Paris et al, 2011). This study also revealed that the policy transfer phase produces novel outcomes from policy innovation and knowledge transfer.…”
Section: Discussionmentioning
confidence: 74%